A PCR-based forward genetics screening, using expression domain-specific markers, identifies mutants in endosperm transfer cell development - Muñiz, Luis M.; Gómez, Elisa; Guyon, Virginie; López, Maribel; Khbaya, Bouchaib; Sellam, Olivier; Peréz, Pascual; Hueros, Gregorio (Frontiers in Plant Science, 2014)
Mutant collections are an invaluable source of material on which forward genetic approaches allow the identification of genes affecting a wide variety of biological processes. However, some particular developmental stages and morphological structures may resist analysis due to their physical inaccessibility or to deleterious effects associated to their modification. Furthermore, lethal mutations acting early in development may escape detection. We have approached the characterisation of 101 maize seed mutants, selected from a collection of 27500 visually screened Mu-insertion lines, using a molecular marker approach based on a set of genes previously ascribed to different tissue compartments within the early developing kernel. A streamlined combination of qRT-PCR assays has allowed us to preliminary pinpoint the affected compartment, establish developmental comparisons to WT siblings and select mutant lines with alterations in the different compartments. Furthermore, clusters of markers co-affected by the underlying mutation were identified. We have analysed more extensively a set of lines presenting significant variation in transfer cell-associated expression markers, and have performed morphological observations, and immunolocalization experiments to confirm the results, validating this approach as an efficient mutant description tool.